Laser-Processed PEN with Au Nanowires Array: A Biocompatibility Assessment - Pryjmaková, Jana; Vokatá, Barbora; Slepička, Petr; Siegel, Jakub (International journal of molecular sciences, 2022)
Although many noble metals are known for their antibacterial properties against the most common pathogens, such as Escherichia coli and Staphylococcus epidermidis, their effect on healthy cells can be toxic. For this reason, the choice of metals that preserve the antibacterial effect while being biocompatible with health cells is very important. This work aims to validate the effect of gold on the biocompatibility of Au/Ag nanowires, as assessed in our previous study. Polyethylene naphthalate (PEN) was treated with a KrF excimer laser to provide specific laser-induced periodic structures. Then, Au was deposited onto the modified PEN via a vacuum evaporation method. Atomic force microscopy and scanning electron microscopy revealed the dependence of the surface morphology on the incidence angle of the laser beam. A resazurin assay cytotoxicity test confirmed safety against healthy human cells and even cell proliferation was observed after 72 h of incubation. We have obtained satisfactory results, demonstrating that monometallic Au nanowires can be applied in biomedical applications and provide the biocompatibility of bimetallic Au/AgNWs.
Keywords: zlato; naftaleny; nanodráty; Polyethylenes; Gold; lidé; Naphthalenes; Lasers; Nanowires; antibakteriální látky; Anti-Bacterial Agents; Escherichia coli; polyethyleny; lasery; Humans